From Traditional Games to Intractive e-Comics: Tungkupan-Based Learning Media for Early Literacy - Rosa, Elvira; Sumarni, Sri; Syarifuddin, Syarifuddin (Edukasi, 2025)
Early childhood literacy skills form a crucial foundation for developing of critical thinking and academic readiness. In Indonesia, low reading interest and a lack of culturally contextualized learning media pose significant challenges. This study addresses this gap by aiming to developing and evaluating the validity, practicality, and effectiveness of an interactive e-comic based on the traditional Palembang game, Tungkupan as an innovative tool for early childhood literacy instruction. Employing a Research and Development (R&D) approach following the ADDIE model, the research involved three expert validators and 27 children from group B at Pembina 7 State Kindergarten in Palembang. Experts rated the product as highly validaverage 80.00% – 83.56%, whileeachers rated it very practicalaverage 91.60%. The effectiveness test, measured by N-Gain, showed a significant increase in scores (from 37.4 to 84.44), with an average N-Gain score of 0.73 (high category), confirming its effectiveness (73.75%) in improving children's literacy skills. These results demonstrate that the interactive Tungkupan based e-comic is a highly valid, practical, and effective medium for both improving early literacy and preserving local cultural heritage.